Magic Mirror: An Intelligent Fashion Recommendation System - Si Liu; Luoqi Liu; Shuicheng Yan (Proceedings - IEEE Computer Society Conference on Pattern Recognition and Image Processing, 2013)
This paper mainly introduces the techniques required for a future system, called Magic Mirror. Imagine when you wake up in the morning and prepare for the coming day, the Magic Mirror will automatically recommend to you the most appropriate styles of hair, makeup, and dressing, according to the events and activities on your calendar, with which it is linked, so that you can present yourself on these occasions with elegant and suitable appearance. The work shall focus on the mathematical models for these tasks, particularly on how to model the relations between low-level human body features, middle-level facial/body attributes, and high-level recommendations. Being automatic and intelligent are the two main characteristics of the system, and this work shall show two prototype sub-systems related with the whole Magic Mirror system.